Spatial inhomogeneities in AlxGa1−xN quantum wells induced by the surface morphology of AlN/sapphire templates. (15th October 2015) - Zeimer, Ute; Jeschke, Joerg; Mogilatenko, Anna; Knauer, Arne; Kueller, Viola; Hoffmann, Veit; Kuhn, Christian; Simoneit, Tino; Martens, Martin; Wernicke, Tim; Kneissl, Michael; Weyers, Markus
Abstract: The effects of the template on the optical and structural properties of Al0.75 Ga0.25 N/Al0.8 Ga0.2 N multiple quantum well (MQWs) laser active regions have been investigated. The laser structures for optical pumping were grown on planar c -plane AlN/sapphire as well as on thick epitaxially laterally overgrown (ELO) AlN layers on patterned AlN/sapphire. Two ELO AlN/sapphire templates were investigated, one with a miscut of the sapphire surface to the m -direction with an angle of 0.25°, the other with a miscut angle of 0.25° to the sapphire a -direction. The MQWs are studied by atomic force microscopy, plan-view cathodoluminescence (CL) at room temperature and 83 K as well as transmission electron microscopy using high-angle annular dark-field imaging and energy-dispersive x-ray spectroscopy. The results are compared to optical pumping measurements. It was found that the surface morphology of the templates determines the lateral wavelength distribution in the MQWs observed by spectral CL mappings. The lateral wavelength spread is largest for the laser structures grown on ELO AlN with miscut to sapphire a -direction caused by the local variation of the MQW thicknesses and the Ga incorporation at macrosteps on the ELO-AlN. A CL peak wavelength spread of up to 7 nm has been found. The MQWs grown on planar AlN/sapphire templates show a homogeneous wavelength distribution. However, due to the high threading dislocation density and the resulting strong nonradiative recombination, laser operation could not be achieved. The laser structures grown on ELO AlN/sapphire show optically pumped lasing with a record short wavelength of 237 nm.